2010
DOI: 10.1002/elsc.200900108
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption study of anionic dyes from aqueous solutions using Bacillus amyloliquefaciens

Abstract: In this study, the biosorption of two commonly used dyes, namely Acid Blue 225 (AB 225) and Acid Blue 062 (AB 062), from aqueous solutions by Bacillus amyloliquefaciens biomass was studied in a batch system with respect to initial dye concentration, pH, adsorbent dosage, and contact time. The biomass exhibited maximum uptake at pH 1 due to its positive nature at acidic pH and the anionic nature of the dyes. Kinetic studies showed that the biosorption of dyes on biomass was a gradual process. An equilibrium was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Dye uptake of Neutral Red displayed a typical bell-shaped pH profile, which exhibited stronger capability over a broad pH range of 1.0-6.0, with an optimum pH at 3.0 for all the treated and untreated P. subacida biomasses. This result was consistent with the previous study [19] which showed lower pH was available for anionic dyes biosorption. Higher dye uptake obtained at relatively lower pH might be due to the electrostatic interaction between negatively charged dye molecules and positively charged fungal cell surface [20].…”
Section: Initial Phsupporting
confidence: 95%
“…Dye uptake of Neutral Red displayed a typical bell-shaped pH profile, which exhibited stronger capability over a broad pH range of 1.0-6.0, with an optimum pH at 3.0 for all the treated and untreated P. subacida biomasses. This result was consistent with the previous study [19] which showed lower pH was available for anionic dyes biosorption. Higher dye uptake obtained at relatively lower pH might be due to the electrostatic interaction between negatively charged dye molecules and positively charged fungal cell surface [20].…”
Section: Initial Phsupporting
confidence: 95%
“…Biofuel produced from biomass has many advantages over traditional fossil fuels, including renewability, greater energy security, and foreign exchange savings. In addition, biofuels from cellulosic feedstocks reduce greenhouse gas (GHG) emissions by about 80% . Use of aquatic biomass, especially algae, as a renewable energy resource is particularly promising. , Unlike land sources of biomass, algae can grow in marine water, fresh water, or even wastewater treatment ponds and, thus, does not compete with other land uses, such as growing crops for food .…”
Section: Introductionmentioning
confidence: 99%
“…Significant parts of several million tons of dyes are usually drained into water systems contaminating them by dyes. So, it is essential to remove this organic contaminant via a suitable therapy method (3,4).Several treatment procedures, such as coagulation, oxidative process, electrolysis sedimentation, and adsorption have been proposed for removing dye from effluent. Among these methods, the adsorption has been found to be very competitive into other processes due to its higher adsorption capacity, lower cost, and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the adsorption has been found to be very competitive into other processes due to its higher adsorption capacity, lower cost, and efficiency. Multiabsorbent methods are applied to remove dye from water and effluent, such as agroindustrial chitosan, minerals, byproduct, bacterial, and fungal biomass, multiwalled carbon nanotubes (MWCNTs), Oxidized multiwalled carbon nanotubes (Oxidized MWCNTs), activated carbon(AC), and Graphene oxide (GO) (3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%